2023
DOI: 10.1177/11772719221144459
|View full text |Cite
|
Sign up to set email alerts
|

What is the Diagnostic Accuracy of Novel Urine Biomarkers for Urinary Tract Infection?

Abstract: Background: Urinary tract infection (UTI) affects half of women at least once in their lifetime. Current diagnosis involves urinary dipstick and urine culture, yet both methods have modest diagnostic accuracy, and cannot support decision-making in patient populations with high prevalence of asymptomatic bacteriuria, such as older adults. Detecting biomarkers of host response in the urine of hosts has the potential to improve diagnosis. Objectives: To synthesise the evidence of the diagnostic accuracy of novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…The biomarkers used in this study [neutrophil gelatinase-associated lipocalin (NGAL), interleukin-8 (IL-8), and interleukin-1-beta (IL-1β)] are essential components of the constitutive immune response in the urinary tract and have been studied in association with UTIs. Importantly, these three biomarkers have also demonstrated utility for the diagnosis of UTIs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. One of our previous studies discovered that NGAL, IL-8, and IL-1β have sensitivities of 82.6%, 91.2%, and 69.8% with specificities of 90.8%, 76.8%, and 96.9%, respectively [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The biomarkers used in this study [neutrophil gelatinase-associated lipocalin (NGAL), interleukin-8 (IL-8), and interleukin-1-beta (IL-1β)] are essential components of the constitutive immune response in the urinary tract and have been studied in association with UTIs. Importantly, these three biomarkers have also demonstrated utility for the diagnosis of UTIs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. One of our previous studies discovered that NGAL, IL-8, and IL-1β have sensitivities of 82.6%, 91.2%, and 69.8% with specificities of 90.8%, 76.8%, and 96.9%, respectively [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 play a protective role during bladder infection, on the other hand in deficiency of IL-6 lead to increases the number of intracellular bacterial communities (IBC) that allow Uropathogenic Escherichia Coli (UPEC) to evade the innate immune system and contribute in urinary tract infection (Edwards et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of such interventions concluded that they may lead to increase of treatments with first-choice antibiotics and a decrease number of treatments with broad-spectrum antibiotics [2]. For example, at-home testing kits may ease the burden GPs face when treating UTIs, as they may aid the accuracy of UTI diagnosis and help to distinguish patients who would benefit from antibiotic treatment from those who do not need it [9,10]. There have been vaccines developed for prevention of recurrent UTIs as well, offering greater protection than antimicrobial prophylaxis [11].…”
Section: Introductionmentioning
confidence: 99%